Additive manufacturing in supply chains - the future of purchasing processes - Stephanie Niehues; Laura Berger; Michael Henke (The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 25, 2018)
Additive manufacturing is one of the leading production technologies when it comes to the efficient production of individual parts. This paper explains how additive manufacturing will influence purchasing processes and network structures of producing companies in future supply chain networks. Therefore, an exploratory research of relevant literature and recent studies in a systematic literature review is conducted, giving an overview of how additive manufacturing will change the processes of purchasing. Traditional purchasing and modern processes affected by the implementation of additive manufacturing are compared, in order to point out differences and new requirements. In the future purchasers have to extend their knowledge of additive manufacturing, to integrate this production technology into their sourcing strategy in an effective way. Technological knowledge and capabilities, supplier relations and internal integration of purchasers need to be improved, to make use of benefits e.g. reduced inventory. This exploration of the impact of additive manufacturing is focused on purchasing processes. Therefore, this paper investigates one special field of the supply chain layer, which is the unique characteristic of this submission. The findings are based on a literature review of studies and specialized literature, an analysis in collaboration with companies was not executed. Additive manufacturing has great advantages in many fields, but it cannot be integrated in supply chain processes with a significant leap forward. The sourcing strategy has to be changed; employees have to be trained, to interact with the new supply chain members and to learn which components can be manufactured additively.
urn:nbn:de:gbv:830-88223314; 10419/209194; https://econpapers.repec.org/RePEc:zbw:hiclpr:25
Keywords: 650; Additive Manufacturing (AM); Purchasing; Supply Chains; Additive Manufacturing in Supply Chains